BDNF Val66Met polymorphism and hippocampal volume in neuropsychiatric disorders: A systematic review and meta-analysis. (August 2015) - Harrisberger, F.; Smieskova, R.; Schmidt, A.; Lenz, C.; Walter, A.; Wittfeld, K.; Grabe, H.J.; Lang, U.E.; Fusar-Poli, P.; Borgwardt, S.
Highlights: Impact of rs6265 on hippocampal volumes in neuropsychiatric patients. Meta-analysis showed no association of hippocampus and genotype in patients. For both genotypes, patients had smaller hippocampal volumes than healthy controls. Abstract: Background: Brain-derived neurotrophic factor (BDNF) is a neurotrophin involved in neurogenesis and synaptic plasticity in the central nervous system, especially in the hippocampus, and has been implicated in the pathophysiology of several neuropsychiatric disorders. Its Val66Met polymorphism (refSNP Cluster Report: rs6265) is a functionally relevant single nucleotide polymorphism affecting the secretion of BDNF and is implicated in differences in hippocampal volumes. Methods: This is a systematic meta-analytical review of findings from imaging genetic studies on the impact of the rs6265 SNP on hippocampal volumes in neuropsychiatric patients with major depressive disorder, anxiety, bipolar disorder or schizophrenia. Results: The overall sample size of 18 independent clinical cohorts comprised 1695 patients. Our results indicated no significant association of left (Hedge's g = 0.08, p = 0.12), right ( g = 0.07, p = 0.22) or bilateral ( g = 0.07, p = 0.16) hippocampal volumes with BDNF rs6265 in neuropsychiatric patients. There was no evidence for a publication bias or any demographic, clinical, or methodological moderating effects. Both Val/Val homozygotes ( g = 0.32, p = 0.004) and Met-carriers ( g = 0.20, p = 0.004) from the patient sample had significantly smaller hippocampal volumes than the healthy control sample with the same allele. The magnitude of these effects did not differ between the two genotypes. Conclusion: This meta-analysis suggests that there is no association between this BDNF polymorphism and hippocampal volumes. For each BDNF genotype, the hippocampal volumes were significantly lower in neuropsychiatric patients than in healthy controls.